Novel Regulation of the Synthesis of α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA) Receptor Subunit GluA1 by Carnitine Palmitoyltransferase 1C (CPT1C) in the Hippocampus - Fadó, Rut (J Biol Chem, 2015)
The regulation of AMPA-type receptor (AMPAR) abundance in the postsynaptic membrane is an important mechanism involved in learning and memory formation. Recent data suggest that one of the constituents of the AMPAR complex is carnitine palmitoyltransferase 1C (CPT1C), a brain-specific isoform located in the endoplasmic reticulum of neurons. Previous results had demonstrated that CPT1C deficiency disrupted spine maturation in hippocampal neurons and impaired spatial learning, but the role of CPT1C in AMPAR physiology had remained mostly unknown. In the present study, we show that CPT1C binds GluA1 and GluA2 and that the three proteins have the same expression profile during neuronal maturation. Moreover, in hippocampal neurons of CPT1C KO mice, AMPAR-mediated miniature excitatory postsynaptic currents and synaptic levels of AMPAR subunits GluA1 and GluA2 are significantly reduced. We show that AMPAR expression is dependent on CPT1C levels because total protein levels of GluA1 and GluA2 are decreased in CPT1C KO neurons and are increased in CPT1C-overexpressing neurons, whereas other synaptic proteins remain unaltered. Notably, mRNA levels of AMPARs remained unchanged in those cultures, indicating that CPT1C is post-transcriptionally involved. We demonstrate that CPT1C is directly involved in the de novo synthesis of GluA1 and not in protein degradation. Moreover, in CPT1C KO cultured neurons, GluA1 synthesis after chemical long term depression was clearly diminished, and brain-derived neurotrophic factor treatment was unable to phosphorylate the mammalian target of rapamycin (mTOR) and stimulate GluA1 protein synthesis. These data newly identify CPT1C as a regulator of AMPAR translation efficiency and therefore also synaptic function in the hippocampus.